Automatic grinding particle size control technology and equipment. (September 2020) - Li, Zhijing; Wang, Yuxuan; Jin, Zhongwu; Zhou, Yinjun
Abstract: The article provides an automatic particle size control technology, which uses advanced particle analysis research technology and modern motor variable frequency control and computer software technology. It can quantify and control the particle size of all products within the grinding capacity of the high-pressure micro-mill. This technology can be widely applied to model sand processing in river engineering model tests, which can greatly improve the processing accuracy, work efficiency, environmental protection performance and reduce energy consumption of ordinary micro-powder mills.